ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR MENJADI AKUNTAN PUBLIK OLEH MAHASISWA JURUSAN AKUNTANSI - SETIAWAN CHAN, ANDI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Students majoring in accounting after graduation will ventually enter the workforce will also be encouraged to choose a career in accounting, one of which is a public accountant. Employment as a public accountant is one of the professional services whose services are needed, especially in terms of examination of financial statements. The purpose of this study was to determine whether the financial reward factor, professional training, professional recognition , social values, work environment, labor market considerations, personality and academic achievement of students influence the election of a public accounting career. The sample used in this study were students majoring in business accounting faculty Unika Widya Mandala Surabaya force 2008. The method of analysis in this study using multiple regression statistical analysis. The conclusion that can be obtained from this study is the training of professionals and personalities significant effect on interest in becoming a public accountant. Variable financial rewards, work environment, labor market considerations and academic achievement no significant effect on interest in becoming a public accountant.